Herramientas de google para el trabajo cooperativo y colaborativo en estudiantes de 6to. grado de Educación Primaria - Carbajal Aguilar, Pedro Eduardo (2021)
Knowing the concept of ICT and the structure, variety and operation of Google Web tools, we can use them as instruments to facilitate the education in educational institutions and facilitate the process of the student population contributing to the improvement of educational quality. This offers us an opportunity to consider a new way of educating by incorporating information and communication technologies in order to reach the objective that is intended to achieve, which is none other than breaking with the paradigm of the current teaching model, whose base is found on interaction schemes between the teacher and the student, everything face to face, in such a way that there is always a unique element that defines the flow of knowledge and information that will always depend on the teacher's methodology and way of teaching, as opposed to an innovative way that allows the students to learn in a natural way, according to their curiosity and skill, always guided by a teacher who also takes the opportunity to acquire new knowledge, making learning a much more enjoyable adventure. To achieve this objective, it is necessary to instruct teachers in the basic use of new technologies, although due to a matter of reality and actuality, the new generations, who are being trained in the teaching area, are already using computer tools, for this reason, it will be much easier to instill in young people the use of Google tools and may be a little more difficult to include in the teaching model of educators these interactive and didactic tools that are used through the internet. It is very difficult to see people nowadays write with the old typewriter, the system has enveloped us all in that immense computing and systematic cloud from the youngest to the grandparents, and it will not be education that moves away from that context, since world situations have favored this new system of Web tools that in turn facilitate the management of information and create speed of communication regardless the place where we are.